Implementation of resistance tester for membrane switch - Buntueng Yana (2018)
Membrane switches are widely used in electronic interface devices, namely computer, point-of-purchase, telecommunication and industrial equipments. To increase the quality of their products, membrane switch manufacturers are required to maintain control over their products with an important quality to be tested which is the membrane switch resistance. However the test equipment is not commercially available. Those manufacturers have to make their own version of membrane switch testers. This paper aims to describe the application of Virtual Instrument in order to build a resistance tester for membrane switch. It also gives an explanation that underlies concepts and production. © 2009 IEEE.